Advances in Databases 28th British National Conference on Databases, BNCOD 28, Manchester, UK, July 12-14, 2011, Revised Selected Papers - Fernandes, Alvaro A. A.; Gray, Alasdair J. G.; Belhajjame, Khalid; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 28th British National Conference on Databases, BNCOD 28, held in Manchester, UK, in July 2011. The 13 revised full papers, 2 short papers, 2 demo papers and 1 poster paper presented together with the abstracts of 2 keynote talks and 1 tutorial paper were carefully reviewed and selected from 44 submissions. The papers cover a wide range of topics such as XML compression, XML updates, column-oriented stores, provenance, warehousing, streamed data, data mashups, dataspaces, sensor network query processing, and pattern-oriented search.
Keywords: Computer science; Data structures (Computer science).; Information systems; Database management; Information storage and retrieval systems; Computer Science; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Data Structures; Data Storage Representation